THE IMPACT OF AUTHENTIC LEADERSHIP AND WORK STRESS ON EMPLOYEE PERFORMANCE: MEDIATING ROLE OF PSYCHOLOGICAL CAPITAL - Farida, Amelia Nurul; Subiyanto, Didik; Hadi, Syamsul (International Conference on Humanity Education and Society (ICHES), 2024)
Employee performance is the result of work performance set by the organization, some literature in improving performance there are still inconsistencies such as authentic leadership in some articles proven to have a positive influence but in other studies it is not proven to have an influence on employee performance. This research is needed to further explore what antecedents have an influence in improving employee performance and adding psychological capital as a mediator. The purpose of this study is to analyze authentic leadership and work stress on employee performance mediated by Psychological Capital. The research methodology involved 124 IT company respondents with sampling techniques using accidental sampling, while data processing used SmartPLS. The results showed that authentic leadership and work stress had no effect on employee performance, but authentic leadership and employee performance had a significant positive effect on psychological capital and work stress had no effect on psychological capital. Mediation analysis shows that psychological capital is able to mediate the effect of authentic leadership, but is unable to mediate work stress on employee performance.